2015
DOI: 10.1007/s40472-014-0042-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Genetic Renal Diseases in Potential Living Kidney Donors

Abstract: Better outcomes for living donor transplantation, together with the shortened waiting time and the increasing gap between supply and demand for kidneys for

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 88 publications
0
5
0
Order By: Relevance
“…With respect to living kidney donors, it is important to ascertain the cause of kidney disease in the related recipient, so that the living donor can be screened for genetic disease if appropriate. 31 Unfortunately, too often the cause of ESRD in patients on the transplant waitlist is unknown or assumed and the increased risk of ESRD postdonation in related living donors may reflect a missed genetic disease. 32,33 In the case of the gene APOL1, the inheritance of two copies of the risk alleles G1 or G2 substantially increases the risk of ESRD in patients of sub-Saharan African ancestry who have hypertension, HIV, sickle cell disease, or systemic lupus erythematosus (SLE).…”
Section: Discussionmentioning
confidence: 99%
“…With respect to living kidney donors, it is important to ascertain the cause of kidney disease in the related recipient, so that the living donor can be screened for genetic disease if appropriate. 31 Unfortunately, too often the cause of ESRD in patients on the transplant waitlist is unknown or assumed and the increased risk of ESRD postdonation in related living donors may reflect a missed genetic disease. 32,33 In the case of the gene APOL1, the inheritance of two copies of the risk alleles G1 or G2 substantially increases the risk of ESRD in patients of sub-Saharan African ancestry who have hypertension, HIV, sickle cell disease, or systemic lupus erythematosus (SLE).…”
Section: Discussionmentioning
confidence: 99%
“…Kidneys from deceased African American donors with two APOL1 risk variants fail more rapidly after transplantation than kidneys from donors with no or one risk allele; however, the APOL1 allele status of the transplant recipient does not affect outcome . Taken together, some have suggested that all African American kidney donors should be screened for these APOL1 risk alleles .…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, establishing and/or confirming the diagnosis of a presumed genetic disease has required Sanger sequencing of the suspected gene for pathogenic variants . When candidate genes are large, like COL4A5 , sequencing is costly and time consuming.…”
Section: Introductionmentioning
confidence: 99%
“…Ascertaining the genetic origin of ESKD in a transplant candidate is essential to evaluate the risk of transmission of kidney disease for the biologically related donor, especially in hereditary nephropathies with age-dependent manifestation [autosomal dominant tubulointerstitial kidney disease (ADTKD)- UMOD ] or diseases with variable expressivity and reduced penetrance such as hepatocyte nuclear factor-1-beta (HNF1B)-associated disease (ADTKD-HNF1B). In families affected by these diseases, gene-specific variant detection has considerable potential for accurate risk and donor suitability assessment among relatives who are candidates for kidney donation [ 32 ].…”
Section: Predicted Clinical Benefit Of Genetic Testingmentioning
confidence: 99%